2020
DOI: 10.1155/2020/8849218
|View full text |Cite
|
Sign up to set email alerts
|

The m6A Methylation-Regulated AFF4 Promotes Self-Renewal of Bladder Cancer Stem Cells

Abstract: The dynamic N6-methyladenosine (m6A) modification of mRNA plays a role in regulating gene expression and determining cell fate. However, the functions of m6A mRNA modification in bladder cancer stem cells (BCSCs) have not been described. Here, we show that global RNA m6A abundance and the expression of m6A-forming enzyme METTL3 are higher in BCSCs than those in non-CSCs of bladder cancer (BCa) cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 40 publications
0
34
0
Order By: Relevance
“…A current research by Gao et al provided unequivocal evidence of m6A involvement in the regulation of BCSCs 39 . The high sphere‐forming ability and aldehyde dehydrogenase (ALDH) activity have been defined as two characteristics to filter the populations of BCSCs 39 . The data showed that RNA m6A abundance and METTL3 level were markedly elevated in the CSCs relative to those in the non‐CSCs of BCa 39 .…”
Section: The M6a‐directed Molecular Basis Involved In the Regulation mentioning
confidence: 94%
See 4 more Smart Citations
“…A current research by Gao et al provided unequivocal evidence of m6A involvement in the regulation of BCSCs 39 . The high sphere‐forming ability and aldehyde dehydrogenase (ALDH) activity have been defined as two characteristics to filter the populations of BCSCs 39 . The data showed that RNA m6A abundance and METTL3 level were markedly elevated in the CSCs relative to those in the non‐CSCs of BCa 39 .…”
Section: The M6a‐directed Molecular Basis Involved In the Regulation mentioning
confidence: 94%
“…The data showed that RNA m6A abundance and METTL3 level were markedly elevated in the CSCs relative to those in the non‐CSCs of BCa 39 . METTL3 inhibition effectively suppressed BCSC self‐renewal, as evidenced by the impaired ALDH activity and sphere‐forming ability 39 . Meanwhile, Gao et al have shown in their previous research that METTL3 induced BCa progression through m6A‐directed posttranscriptional regulation of AF4/FMR2 family member 4 (AFF4) 40 .…”
Section: The M6a‐directed Molecular Basis Involved In the Regulation mentioning
confidence: 98%
See 3 more Smart Citations